Organizational and legal mechanism of the environmental protection - Гетьман, А. П. (Problems of legality, 2014)
Organizational and legal mechanisms of environmental protection are defined by the author of the article as a mechanism of organization and system of activities of state executive power bodies and local self-government bodies in the field of environmental public relations arising in connection with environmental protection and environmental safety provision. The rules of administrative law are its legal basis, alongside with the norms of environmental law. The former designed to reflect the specifics of the subject, objects, subjects and principles of legal regulation of social relations in this area. The latter define common goals, objectives and functions of state public relations management nature.